Sovereign green bonds as an unconventional tool to address climate change - Yadav, Anuradha; Manda, Vijaya Kittu; Shivani; Sangwan, Vikramaditya; Vambol, Sergij (Ecological Questions, 2024)
Creative efforts are necessary as global efforts seek to undertake projects focused on environmental, social, and governance (ESG) initiatives. Among various financial products that provide funding for projects, green bonds, particularly sovereign green bonds (SGB or SGrB) issued with sovereign guarantees by central governments, have gained prominence. Proceeds from SGBs are used to finance green projects such as non-conventional and renewable energy projects, alternative energy solutions, greenhouse gas emission reduction, climate change mitigation, or reduced use of carbon-based energy sources. SGB will receive increasing global attention as governments attempt to meet UN climate change goals. This research uses descriptive research methodology to examine the evolution, operational aspects, challenges, and investor expectations associated with SGrBs by taking India as a case. The study period is taken from 2016 to 2023. It used a conceptual approach to discuss the market's evolution. The findings highlight how SGBs provide an unconventional way to link green finance with ecological priorities by combining fiscal policy, investment and science-based solutions. The insights are intended to inform future SGB frameworks and strategies to target funded green growth towards pressing global sustainability issues.